2011
DOI: 10.1007/s11581-010-0511-5
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric and transport properties of N-Butyl-N-methylpyrrolidinium bis(Trifluoromethanesulfonyl)imide–methanol binary mixtures

Abstract: Densities, viscosities, and ionic conductivities were measured for the binary mixtures containing the ionic liquid Nbutyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl) imide and methanol over the entire range of compositions at the temperature varying from 253.15 to 318.15 K. The densities and viscosities decrease monotonously with temperature and the content of ionic liquids (ILs). Furthermore, excess isobaric expansion coefficient has been calculated from the experimental densities. The dependence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…As these plots show, the ionic conductivity increases when the temperature rises in all the systems, because temperature produces an increment of the mobility of the ions. 11,13 It is also remarkable that ionic conductivities of the mixtures are higher than pure compounds values. 11,14 All the experimental curves have the same shape and can be divided in two parts which are separated by the maximum of the graph: at high ionic liquid concentrations, ionic conductivities are small because the viscosity of the mixture is too large, when small quantities of the organic solvent are added, the viscosity decreases and the mobility of charge carriers rises, consequently ionic conductivity continuously increases until it reaches its maximum.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As these plots show, the ionic conductivity increases when the temperature rises in all the systems, because temperature produces an increment of the mobility of the ions. 11,13 It is also remarkable that ionic conductivities of the mixtures are higher than pure compounds values. 11,14 All the experimental curves have the same shape and can be divided in two parts which are separated by the maximum of the graph: at high ionic liquid concentrations, ionic conductivities are small because the viscosity of the mixture is too large, when small quantities of the organic solvent are added, the viscosity decreases and the mobility of charge carriers rises, consequently ionic conductivity continuously increases until it reaches its maximum.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…10 However, the experimental measurements of the ionic conductivity of liquid mixtures containing ILs are scarce in the literature. Zarrougui et al 11 presented a study of volumetric and transport properties of N-butyl-N-methylpyrrolidinium bis trifluoromethanesulfonyl imide with methanol in the temperature range 253.15 K to 318.15 K. Toumi et al 12 studied the ionic conductivity as a function of temperature for the liquid mixture triethylamine plus KCl aqueous solution. Zhang et al 13 measured the ionic conductivity of solutions of pyridinium based ionic liquids with methanol, ethanol, acetonitrile, and propylene carbonate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The authors assumed a complete dissociation of the IL into ions to explain the anomalous behavior. In the study by Zarrougui et al, 19 the authors reported viscosities and ionic conductivities of IL− methanol mixtures and noted that the viscosity of the mixture increases marginally up to an IL concentration of 1. increases dramatically for concentrations exceeding this limit.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The authors assumed a complete dissociation of the IL into ions to explain the anomalous behavior. In the study by Zarrougui et al, the authors reported viscosities and ionic conductivities of IL–methanol mixtures and noted that the viscosity of the mixture increases marginally up to an IL concentration of 1.5 M but increases dramatically for concentrations exceeding this limit. Similarly, the ionic conductivity shows an increase to 1.1 M IL concentration, beyond which the conductivity decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquid is usually mixed with organic solvents to reduce viscosity and improve electrical conductivity. For example, Rilo et al dissolved 1-alkyl-3-methyl imidazolium tetrafluoroborate ([C n MIM]­[BF 4 ], n = 2, 4, 6, 8) in ethanol and found the electrical conductivity of the solution was significantly improved compared to the pure IL. Zarrougui et al measured the electrical conductivity of N -butyl- N -methylpyrrolidinium bis­(trifluoro-methanesulfonyl) imide ([Pyr 14 ]­[TFSI]) + methanol mixture, and they found there was a maximum value of electrical conductivity for the solution. Similarly, dissolved ionic liquid in mixed organic solvents can also improve the performance of the electrolyte.…”
Section: Introductionmentioning
confidence: 99%